An Empirical Analysis of Household Debt Behavior Determinants - Herispon Herispon (Institute for Economic and Social Research, 2019)
This study identifies the determinants of debt behaviors and their effects on household consumption. We surveyed households in Riau, particularly in Pekanbaru and its neighboring areas, using purposive sampling and collected 390 useable responses. Our findings show that of the ten determinants considered, debt behavior can be explained by five determinants: (i) imitated lifestyle and consumerism, (ii) ability to manage money from debt, (iii) effects of promotion on the internet and visual media, (iv) monthly income, and (v) increasing household expenses and dependants. Implications of the findings are discussed.